Towards standardized patient reported physical function outcome reporting: linking ten commonly used questionnaires to a common metric. - Oude Voshaar, M. A. H.; Vonkeman, H. E.; Courvoisier, D.; Finckh, A.; Gossec, L.; Leung, Y. Y.; Michaud, K.; Pinheiro, G.; Soriano, E.; Wulfraat, N.; Zink, A.; van de Laar, M. A. F. J. (Quality of Life Research, 2019)
Objectives: Outcomes obtained using different physical function patient reported outcome measures (PROMs) are difficult to compare. To facilitate standardization of physical function outcome measurement and reporting we developed an item response theory (IRT) based standardized physical function score metric for ten commonly used physical function PROMs.Methods: Data of a total of 16,386 respondents from representative cohorts of patients with rheumatic diseases as well as the Dutch general population were used to map the items of ten commonly used physical function PROMs on a continuous latent physical function variable. The resulting IRT based common metric was cross-validated in an independent dataset of 243 patients with gout, osteoarthritis or polymyalgia in which four of the linked PROMs were administered.Results: Our analyses supported that all 97 items of the ten included PROMs relate to a single underlying physical function variable and that responses to each item could be described by the generalized partial credit IRT model. In the cross-validation analyses we found congruent mean scores for four different PROMs when the IRT based scoring procedures were used.Conclusions: We showed that the standardized physical function score metric developed in this study can be used to facilitate standardized reporting of physical function outcomes for ten commonly used make physical function PROMs.